Efficient use of waste photopolymer plates in bitumen modification and an alternative styrene-butadiene-styrene modification method - Kok, Baha Vural; Yetkin, Zulfu; Yalcin, Erkut; Ozdemir, Ahmet Munir (Springer, 2024)
Photopolymers, which are composed of monomer, oligomer polymer, and their combinations and exhibit photochemical reactions when exposed to light, are now commonly employed in 3D printers, particularly in the flexographic printing industry, and are becoming waste. The utilization of waste solid sheet Photopolymer Plates (PhP) for bitumen modification is an efficient way of disposing of post-consumer items and an alternate method of obtaining new, high-quality modifiers. The consequences of using waste PhP in bitumen modification, both independently and in conjunction with Styrene-Butadiene-Styrene (SBS) were explored. By combining PhP and SBS, it is hoped that savings can be made without sacrificing performance due to the high rate of single SBS modification. The modified binders prepared using PhP and SBS both separately and together were subjected to conventional and rheological tests. The performance of 5% SBS modification could not be achieved at the highest rate that PhP can be used alone without creating a workability problem. The use of 5-7% PhP in combination with 2% SBS outperformed the single 5% SBS modification. This combined binder did not cause workability problems and showed good low and high-temperature behavior and was found to be an economical alternative to SBS modification.
Keywords: Bitumen; Waste photopolymer; SBS; Modification; Rheology